THE INTELLIGENCE OF NATURE: HOW AI IS REDEFINING ORGANIC PRODUCTION IN 2026 - Kholmukhammedov Abdulaziz; Avazbekova Jasmina (TADQIQOTLAR, 2026)
Abstract: As the global organic market nears 136 billion, manufacturers face a "scaling gap" driven by high labor costs and strict chemical-free mandates. This article explores the shift toward Industry 5.0, where AI ensures predictive integrity through technologies like Hyperspectral Imaging and E-Noses, achieving 99% detection accuracy for contaminants. We analyze the financial transition from variable labor to fixed tech investments, which typically cuts food waste by 30–40%. Finally, we examine the regulatory landscape, including the EU AI Act and ISO/IEC 42001, highlighting how AI-driven precision enables large-scale, sustainable organic production while maintaining the "natural" promise. By synthesizing these technical and economic perspectives, the study provides a roadmap for producers navigating the digital transformation of heritage farming practices.